2022
DOI: 10.1007/s00500-022-07457-2
|View full text |Cite
|
Sign up to set email alerts
|

An automatic and intelligent brain tumor detection using Lee sigma filtered histogram segmentation model

Abstract: Brain tumors are the second important origin of death worldwide. The early and exact identification of brain tumors is significant for the healing process. With accelerating diagnoses, medicine as well as pricing, quantum computing permits disruptive cases to providers. Quantum improved deep learning was especially significant to the sector. However, the conventional machine learning method faces main challenges to achieve accurate brain tumor detection with MRI images. Therefore, this paper proposes a novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…The study by Kurian and Juliet [30] suggests a unique method for quickly and accurately identifying brain cancers termed Lee sigma filtered histogram segmentation (LSFHS). Preprocessing, segmentation, feature extraction, and classification are the foundations of the LSFHS approach.…”
Section: Related Workmentioning
confidence: 99%
“…The study by Kurian and Juliet [30] suggests a unique method for quickly and accurately identifying brain cancers termed Lee sigma filtered histogram segmentation (LSFHS). Preprocessing, segmentation, feature extraction, and classification are the foundations of the LSFHS approach.…”
Section: Related Workmentioning
confidence: 99%
“…To separate an image into two pieces, imaging segmentation is utilized in the field of medical images. After the process of segmentation, the brain regions are recognized by the classification approach [13,14]. Various approaches and algorithms are established for tumor segmentation because of the intricate segmentation procedure in the MRI image [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of classifying brain tumors in public datasets, a hybrid CNN is designed in. [20][21][22] They demonstrated that by tuning the CNN's hyperparameters with a specialized approach, accuracy can be improved.…”
Section: Introductionmentioning
confidence: 99%